4-D Model : Teaching Materials To Reading Comprehension With DRTA Strategy For Elementary School Students - Kurniaman, Otang; Noviana, Eddy; Guslinda, Guslinda; Zufriady, Zufriady (Universitas Pahlawan Tuanku Tambusai, 2021)
Reading is a skill that must be mastered by elementary school students because it can increase a person's reasoning for that a teacher must be a bridge in transferring knowledge by using teaching materials with DRTA strategies. Research method 4-D development with 4 stages define, design, develop, and disseminate. Teaching materials that have been validated by experts and practitioners with validation results of content eligibility with an average of 88.3 are very valid, linguistic aspects with an average of 91.6 are very valid, presentation aspects with an average of 90 are very valid, and aspe graphic of 87.5 is very valid.. After the validated teaching materials were tested in the class using a quasi-experimental method to obtain an increase in experimental class reading comprehension 18.75% higher than the increase in the control class with a 12.5% increase in class. To test whether there is a significant difference in the gain value tested by using normality and homogeneity tests, after the results are obtained, it is re-tested using the average difference test with the results of t_counts = 0.26 and t_table= 2.00 so that it can be concluded that the ability to read comprehension does not exist significant difference.